2016
DOI: 10.1016/j.math.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

How should we teach lumbar manipulation? A consensus study

Abstract: This Delphi study successfully identified key characteristics of patient position and operator position and motion for effective delivery of side-lying lumbar spine manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(55 reference statements)
1
9
0
2
Order By: Relevance
“…Through a Delphi process, O'Donnell et al investigated what educators and clinicians considered to be important characteristics of the patients and clinicians' positions before and during SMT. Results showed that patient comfort was identified as important, with a high level of agreement ( 32 ). In addition to this Delphi, Pasquier et al investigated associations between objective SMT biomechanical parameters and subjective assessments such as patient comfort perceived by patients, clinicians, and expert assessors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a Delphi process, O'Donnell et al investigated what educators and clinicians considered to be important characteristics of the patients and clinicians' positions before and during SMT. Results showed that patient comfort was identified as important, with a high level of agreement ( 32 ). In addition to this Delphi, Pasquier et al investigated associations between objective SMT biomechanical parameters and subjective assessments such as patient comfort perceived by patients, clinicians, and expert assessors ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the level of comfort during SMT was assessed following the intervention, using a 100-mm scale, a higher score indicating a very comfortable procedure and a lower score a very uncomfortable one. This criterion was identified by O'Donnell et al as an important patient characteristic regarding SMT performance ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is vital that students have adequate practice time and appropriate feedback in the academic setting from educators with expertise in TJM, in order to successfully acquire and retain these motor skills. Consistency among educators, and use and development of best teaching methods and practices based on motor learning and educational theory play an important role in developing TJM skills [16,28,29,31,32]. It is important that academic programs provide students with a strong foundation in manual therapy skills and for clinical education experiences to provide students with opportunities for mentorship by clinical instructors with advanced manual therapy training in order to further develop their competency.…”
Section: Recommendationsmentioning
confidence: 99%
“…척추교정실행은 다양한 부위에 적용이 가능하며 적용 부위에 따라 대상자의 자세로 달라진다. 그 중 옆으로 누운 골반의 척추교정적용은 힘을 효과적으로 전달하기 위해 초심자 물리치료사가 많은 훈련과 연습이 필요로 하는 복잡한 운동 기술이며 [16]. Triano와 Descarreaux [17], 요천추의 척추교정적용은 치료사의 자세변화가 작 은 흉추 적용에 비해 더욱 복잡한 다중 협응 운동이라 고 정의하였다.…”
unclassified
“…Triano와 Descarreaux [17], 요천추의 척추교정적용은 치료사의 자세변화가 작 은 흉추 적용에 비해 더욱 복잡한 다중 협응 운동이라 고 정의하였다. O'Donnell과 Smith [16]의 요천추 척추 교정에 대한 연구에 의하면 추력의 힘 발생을 위한 테 이블 높이가 중요하다는 것에 모든 임상의들이 동의한 다고 기술하였고, 테이블 높이에 관하여 시술자의 전상 장골극(anterior superior iliac spine)과 환자의 테이블과 비접촉면의 전상장골극 위치와 만나는 지점의 높이에서 척추교정이 이루어져야 한다는 주장이 있지만 이것은 일부 임상의의 의견이다 [16].…”
unclassified